Synthesis and Biological Evaluation of N-Alkoxyphenyl-3-hydroxynaphthalene-2-carboxanilides - Gonec, Tomas; Zadrazilova, Iveta; Nevin, Eoghan; Kauerova, Tereza; Pesko, Matus; Kos, Jiri; Oravec, Michal; Kollar, Peter; Coffey, Aidan; O'Mahony, Jim; Cizek, Alois; Kralova, Katarina; et al. (Molecules (Basel, Switzerland), 2015)
A series of fifteen new N-alkoxyphenylanilides of 3-hydroxynaphthalene-2-carboxylic acid was prepared and characterized. Primary in vitro screening of the synthesized compounds was performed against Staphylococcus aureus, three methicillin-resistant S. aureus strains, Mycobacterium tuberculosis H37Ra and M. avium subsp. paratuberculosis. Some of the tested compounds showed antibacterial and antimycobacterial activity against the tested strains comparable with or higher than that of the standards ampicillin or rifampicin. 3-Hydroxy-N-(2-propoxyphenyl)naphthalene-2-carboxamide and N-[2-(but-2-yloxy)-phenyl]-3-hydroxynaphthalene-2-carboxamide had MIC = 12 µM against all methicillin-resistant S. aureus strains; thus their activity is 4-fold higher than that of ampicillin. The second mentioned compound as well as 3-hydroxy-N-[3-(prop-2-yloxy)phenyl]-naphthalene-2-carboxamide had MICs = 23 µM and 24 µM against M. tuberculosis respectively. N-[2-(But-2-yloxy)phenyl]-3-hydroxynaphthalene-2-carboxamide demonstrated higher activity against M. avium subsp. paratuberculosis than rifampicin. Screening of the cytotoxicity of the most effective antimycobacterial compounds was performed using THP-1 cells, and no significant lethal effect was observed for the most potent compounds. The compounds were additionally tested for their activity related to inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. N-(3-Ethoxyphenyl)-3-hydroxynaphthalene-2-carboxamide (IC50 = 4.5 µM) was the most active PET inhibitor. The structure-activity relationships are discussed.
Keywords: Anilides; viabilita buněk; Cell Line; photosynthetic electron transport inhibition; Rifampin; in vitro cytotoxicity; rifampin; fotosyntéza; mikrobiální viabilita; chloroplasty; naftaleny; Structure-Activity Relationship; Photosynthesis; monocyty; Naphthalenes; antibakteriální látky; Microbial Sensitivity Tests; Cell Survival; transport elektronů; Chloroplasts; in vitro antibacterial activity; Spinacia oleracea; Mycobacterium avium subsp. paratuberculosis; ampicilin; vztahy mezi strukturou a aktivitou; Electron Transport; Microbial Viability; lidé; Methicillin-Resistant Staphylococcus aureus; anilidy; Anti-Bacterial Agents; Humans; hydroxynaphthalene-2-carboxanilides; mikrobiální testy citlivosti; Monocytes; buněčné linie; structure-activity relationships; in vitro antimycobacterial activity; Ampicillin; methicilin rezistentní Staphylococcus aureus; Mycobacterium tuberculosis